PWE-021 Secondary care costs in oesophagogastric cancer in the UK: a single centre micro-costing study. (28th May 2012) - Stern, N; Bassi, A; Bodger, K
Abstract : Introduction: Published data describing the scale, profile and determinants of healthcare resource use for oesophago-gastric cancer (OGC) are scarce, particularly for the UK. The National Cancer Plan (2000) encouraged greater use of imaging for staging and increased use of oncological therapies but the major modalities of palliation and curative surgery have changed little over the last decade. We have reported how emergency presentation predicts a poor outcome 1 and now aimed to study the effect of this mode of presentation on resource use and cost. Methods: Using cohorts of all patients presenting with OGC to a single university hospital trust (Aintree University Hospital, Liverpool, UK) over two, 2-year periods (July 1997–June 1999 and Jan 2001–Dec 2002) we audited all resource use from referral to diagnosis and 12 months post-diagnosis or death (whichever was sooner). Diagnostic and staging investigations, in-patient bed days and treatments including surgical, oncological and endoscopic were all itemised. Patient treatment was categorised according to initial intent. Individual hospital based unit costs or HRG tariffs (2010/2011 financial year) were applied to derive per-patient costs for the cohorts. Results: Of 333 patients identified, 320 had complete data to enable cost analysis. Median cost per-patient was £11 965.94 with annualised costs to our institution of £1.2 million. Potentially curative treatment accounted for 32.5% of institutional costs, palliation 56.2% and supportive care 11.3%. Per-patient costs [median (IQR)]: Curative treatment: £11 863.80 (9701–17 430); Palliative treatments: £14 288.52 (10 016–22 710); Supportive care only: £6619.96 (3567–11 778). Emergency presentations (31.2% of cases) consumed 30.8% of cost despite shorter survival with significant increased costs per live day (£148.14 vs 71.61, p<0.001), mostly due to longer inpatient stays. Linear regression of log transformed costs confirms that emergency presentation increased cost per live day independently of age or potentially curative treatment. Endoscopic interventions were used in 33.4% patients. Conclusion: Managing OGC has a significant impact on healthcare resources with most expenditure is for those treated with palliative intent. Presenting as an emergency increases costs per live-day compared to elective presentation. These primary data can support modelling studies of cost-effectiveness of rival programmes or treatments for OGC. Competing interests: None declared. Reference: 1. Shawihdi M, Stern N, Thompson E, et al. Emergency admission as a route for oesophago-gastric cancer diagnosis: a marker of poor outcome and a candidate quality indicator for local services. Gut 2011;60 (Suppl 1):A30–1.